2009
DOI: 10.1007/s11295-009-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and genetic structure of African oil palm diversity suggests new approaches to breeding

Abstract: Since the 1960s, there has been very little diversification of oil palm (Elaeis guineensis) seed production, with mainly Deli × La Mé and Deli × Congo type crosses. The Deli origin, which was introduced from Africa into Indonesia in 1848, is unavoidable in breeding. In order to understand the complementarity between the Africa and "Asia" origins, and to diversify the genetic base of oil palm production, the structure of the genetic resources involved in the history of oil palm breeding in relation to African g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 20 publications
9
63
2
4
Order By: Relevance
“…It was of interest to note that cluster analysis did not entirely group genotypes according to their provenances. This result is congruent with Bakoumé et al (2015) and Cochard et al (2009) who found that accessions from Nigeria, Cameroon, and Angola were grouped in the same cluster. Furthermore, it has also been suggested that the possible origin of Deli materials is in a region covering Nigeria, Cameroon, Zaire, and Angola (Bakoumé et al, 2015).…”
Section: Genetic Differentiation and Relatedness Among Nifor And Mpobsupporting
confidence: 89%
See 2 more Smart Citations
“…It was of interest to note that cluster analysis did not entirely group genotypes according to their provenances. This result is congruent with Bakoumé et al (2015) and Cochard et al (2009) who found that accessions from Nigeria, Cameroon, and Angola were grouped in the same cluster. Furthermore, it has also been suggested that the possible origin of Deli materials is in a region covering Nigeria, Cameroon, Zaire, and Angola (Bakoumé et al, 2015).…”
Section: Genetic Differentiation and Relatedness Among Nifor And Mpobsupporting
confidence: 89%
“…The number of alleles per locus also could have depended on the SSR markers used. In fact, Cochard et al (2009) and Bakoumé et al (2015) used comparable sets of SSR markers different from the one employed in the present study.…”
Section: Mean Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on diversity suggests that the germplasm of oil palm is structured into three groups (Cochard et al, 2009). The native populations from Africa are genetically structured into two groups from regions separated by the Dahomey Gap, a dry zone that separates regions of equatorial climate forests in Western Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, oil palm improvement programme in NIFOR and elsewhere aims at producing high quality oil yielding tenera (D × P) planting materials. Therefore, the maintenance of adequate genetic variability among parent populations used for hybrid seed production is critical for maximum utilization of heterosis and sustained genetic progress in the selection cycle [8].…”
Section: Introductionmentioning
confidence: 99%